GPX4 Downregulation Induces Platelet Ferroptosis in Systemic Lupus Erythematosus - Zhirui Zhou; Fangyuan Yang; Ying Huang; Jian Zhuang; Yuxuan Yuan; Jinli Wei; Yi He (Journal of Clinical Rheumatology and Immunology)
Background: Ferroptosis is a recently discovered type of regulated necrosis and glutathione peroxidase 4 (GPX4) has been recognized as a key enzyme that protects against ferroptosis. However, the role of platelet GPX4 in systemic lupus erythematosus (SLE) has not been explored. In this study, GPX4 levels in platelets were measured and the correlation with clinical features were analyzed. Methods: Platelet GPX4 protein expression was detected by Western blot and immunofluorescence in 37 SLE patients and 23 healthy controls. Clinical data were recorded at time points of blood sampling. Platelet activation was analyzed by flow cytometry, LDH release by LDH release assay and plasma oxidized DNA levels by a general 8-OHdG ELISA kit. Results: Patients with SLE had significantly decreased expression of platelet GPX4 and increased percentage of platelet activation as compared with healthy controls. Furthermore, levels of platelet GPX4 were negatively correlated with SLEDAI-2K score, 24-hour urine protein and oxidized DNA. Low GPX4 expression were associated with skin and joint involvements of SLE patients. Interestingly, deferoxamine (DFO), a ferroptosis inhibitor, could protect SLE platelets from death. Conclusions: These findings confirmed that downregulated GPX4 protein in platelets of SLE patients negatively correlated with plasma oxidized DNA, SLE disease activity and 24-hour urine protein, suggesting the potential role of platelet ferroptosis in oxidized DNA release and the pathogenesis of SLE.